Coreceptor Tropism in Human Immunodeficiency Virus Type 1 Subtype D: High Prevalence of CXCR4 Tropism and Heterogeneous Composition of Viral Populations - Huang, Wei; Eshleman, Susan H.; Toma, Jonathan; Fransen, Signe; Stawiski, Eric; Paxinos, Ellen E.; Whitcomb, Jeannette M.; Young, Alicia M.; Donnell, Deborah; Mmiro, Francis; Musoke, Philippa; Guay, Laura A.; et al. (Journal of virology, 2007)
In human immunodeficiency virus type 1 (HIV-1) subtype B, CXCR4 coreceptor use ranges from ∼20% in early infection to ∼50% in advanced disease. Coreceptor use by non-subtype B HIV is less well characterized. We studied coreceptor tropism of subtype A and D HIV-1 collected from 68 pregnant, antiretroviral drug-naive Ugandan women (HIVNET 012 trial). None of 33 subtype A or 10 A/D-recombinant viruses used the CXCR4 coreceptor. In contrast, nine (36%) of 25 subtype D viruses used both CXCR4 and CCR5 coreceptors. Clonal analyses of the nine subtype D samples with dual or mixed tropism revealed heterogeneous viral populations comprised of X4-, R5-, and dual-tropic HIV-1 variants. In five of the six samples with dual-tropic strains, V3 loop sequences of dual-tropic clones were identical to those of cocirculating R5-tropic clones, indicating the presence of CXCR4 tropism determinants outside of the V3 loop. These dual-tropic variants with R5-tropic-like V3 loops, which we designated “dual-R,” use CCR5 much more efficiently than CXCR4, in contrast to dual-tropic clones with X4-tropic-like V3 loops (“dual-X”). These observations have implications for pathogenesis and treatment of subtype D-infected individuals, for the association between V3 sequence and coreceptor tropism phenotype, and for understanding potential mechanisms of evolution from exclusive CCR5 use to efficient CXCR4 use by subtype D HIV-1.